A chipless RFID tag for smart temporal applications. Issue 8 (20th April 2018) - Zahra, Anum; Shahid, Humayun; Ali Riaz, Muhammad; Amin, Yasar; Tenhunen, Hannu
Abstract: A compact, robust, chipless radio frequency identification (RFID) tag is proposed. Resonant elements patterned in a concentric fashion encode data in the spectral domain employing frequency shift encoding. The proposed tag encodes 28.25 data bits over a miniscule physical footprint of 25 × 25 mm 2 . The formulated scheme is demonstrated to be viable for encoding of temporal variables. The electromagnetic performance of the presented design is investigated for different laminates: Rogers RT/duroid® 5880 and Taconic TLX‐0. Multiple tag prototypes employing a variety of substrates are realized and evaluated for in‐laboratory performance. The proposed design is compared with existing work reported in literature. Code density of 4.52 bits/cm 2 has been successfully achieved. The tag design operates from 3.07 to 10.6 GHz and is readily realizable on flexible laminates. Smart retail, intelligent packaging, adaptive ticketing, and similar time‐related applications can be materialized using the proposed tag.